Development of an effective assessment and training support system for cognitive ability for special children - Tan, Meng Kuan (World Scientific and Engineering Academy and Society, 2010)
In definition, special children include children who are having Down syndrome, autism, global delay, epilepsy, slow learner and others. In this study, the special children are focused on children with Down syndrome. Down syndrome occurs due to an extra copy of chromosome 21 in the children's chromosome. Early intervention Program (EIP) is a systematic program with therapy, exercises, and activities which designed to help children especially special children. Cognitive development is the construction of thought processes, which is one of the most important skills that have to be developed for Down syndrome children in order to lead a normal life. This support system is focused mainly to help them improving their logical thinking and memory skills. This cognitive assessment and training support system utilizes the radio frequency identification (RFID) technology implemented in C Sharp programming language. The completed system was then tested and feedback was obtained from parents or trainers of Down syndrome children. The results show that the system can generate results in graphical form stably and training for improving the cognitive ability of the children is reliable based on global recognized curriculum. In conclusion, the system can be used in order to help trainers or parents to improve the cognitive ability of children with Down syndrome.